Perpustakaan digital: Akses buku dan pengetahuan di genggaman tangan - nadira, bella (Maliki Interdisciplinary Journal, 2025)
Digital libraries offer a web-based library service model that allows users to access collections of e-books, journals, and various information sources anytime and anywhere. Developing a web-based digital library application using the Waterfall method has resulted in significant improvements in accessibility and user experience through a more user-friendly and interactive interface. Additionally, digital libraries greatly support the academic world by providing e-books, e-journals, and online databases that can be accessed remotely without location restrictions. Users can search metadata (title, author, abstract, subject) and use advanced search features to quickly and accurately find information. However, challenges remain, such as infrastructure limitations and digital literacy, as well as the need for continuous evaluation and optimization of the application's interface and features. Therefore, further development should focus on enhancing user capabilities (user-centered design), digital training, and copyright policies and data privacy protection. In this way, digital libraries can become a cornerstone of equitable access to knowledge and support modern learning.